Optical methods for measurement of fatigue crack closure: moire interferometry and digital image correlation - Nowell, D; Paynter, R; De Matos, P (2010)
This paper describes three different optical techniques for the measurement of in-plane displacements close to the crack tip which can then be used to determine the presence of crack closure in propagating fatigue cracks. Conventional temporal phase shifting moiré interferometry is described first, followed by an improvement to this technique, load sequence phase stepping, which allows data to be collected much more frequently during a load cycle. Finally, more recent measurements using digital image correlation are reported. Results from all three techniques are compared and the advantages and disadvantages of each approach are discussed. © 2010 Blackwell Publishing Ltd.